A cohort study of comorbidity in patients with granulomatosis with polyangiitis. (23rd October 2017) - Li, Lin; Neogi, Tuhina; Jick, Susan
Abstract: Objectives: To evaluate the associations between granulomatosis with polyangiitis (GPA) and a wide range of comorbidities in patients with GPA compared with population-based non-vasculitis patients. Methods: Using the UK-based Clinical Practice Research Datalink we identified 570 incident patients with GPA in 1990–2014, and for each case, we selected up to 10 random non-vasculitis patients matched for age, sex, practice and years of history before the date of first GPA diagnosis. We compared the distribution of 13 pre-existing comorbidities and estimated the risk of each incident comorbidity after the cohort entry between GPA and non-vasculitis patients. Results: Patients with GPA were more likely to have a history of hypothyroidism at their initial diagnosis compared with non-vasculitis patients. Patients with GPA had increased risk of incident venous thromboembolism any time during follow-up compared with non-vasculitis patients, particularly during the first 3 years of follow-up: hazard ratio (HR) of 5.24 (95% CI: 2.83, 9.71). Risks were also increased for hypertension (HR = 2.45, 95% CI: 1.84, 3.26), type 2 diabetes (HR = 2.13, 95% CI: 1.36, 3.32), dyslipidaemia (HR = 1.98, 95% CI: 1.29, 3.04) and depression (HR = 1.77, 95% CI: 1.10, 2.86) among GPA patients during the first 3 years of follow-up, but not after 3 years post-diagnosis. Conclusion: Patients with GPA had a higher prevalence of hypothyroidism before the initial diagnosis, a strong risk of developing venous thromboembolism during follow-up and increased risks of hypertension, dyslipidaemia, type 2 diabetes and depression in the first few years after diagnosis, compared with non-vasculitis population.